The influence of organization factors on information technology (IT) project management success in Malaysia government agencies / Bukhary Mamat Ramli@Ramli - Mamat Ramli@Ramli, Bukhary (2013)
The organizational factors are one of the most importance issues to be looked into when implementing computer-base information systems in Malaysia government agency (Muhd-Yusof, 2005), therefore in this research will look critically at the factors related on organizational. Furthermore, there is still a lack of empirical studies that integrate organizational factors and IT project success particularly in Malaysia. This aim for this study is to identify factors related on organization that influence the success of the IT project management. Base on literature reviews, six organization factors and three IT project management success criteria were used in developing the framework for this study. The framework is used to investigate the relationship between the identified organizational factors and IT project management success criteria in Malaysia government agency located at Federal Territory of Kuala Lumpur and Putrajaya. The organizational factors are top management support, organization structure, goal alignment, resources allocated, user participation and organization culture, whereas the IT project management success criteria include time, cost and objectives. The study found that organization structure and goal alignment in organizational factors are significantly influence in the success of the IT project management in Malaysia government agency. By identify the factors, it may for provide a guidelines of successful IT project management in order to helps the project management professionals to understand and implement in project management more successfully.